Utilization of Mosques as a Learning Facility for Religious Education at Taufik Mosque, Tegal Rejo Village - Alhafiz, Jehanda; Kasduri, Mario (Journal of Social Work and Science Education, 2025)
The purpose of this study was to analyze the utilization of Taufik Mosque in Tegal Rejo Village as a means of religious education learning and to identify the challenges faced in increasing its effectiveness. This study used a qualitative methodology with a case study approach, where data were obtained through interviews, observations, and documentation. Informants in this study included mosque managers, teachers, and local community members. The results of the study indicate that although Taufik Mosque has great potential with complete facilities and a strategic location, there are still many challenges faced, such as low community participation, limited human resources, and lack of interesting programs for children. In addition, low public awareness of the importance of religious education is a major problem. To increase its effectiveness, better collaboration is needed between the community, religious leaders, and mosque managers, as well as the development of more interesting and relevant programs using technology and interactive learning methods. This study suggests the need to increase socialization about the importance of religious education and the active role of parents in supporting religious activities in the mosque.